Inhibition of the Mitochondrial Glutamate Carrier SLC25A22 in Astrocytes Leads to Intracellular Glutamate Accumulation - Goubert, Emmanuelle; Mircheva, Yanina; Lasorsa, Francesco M.; Melon, Christophe; Profilo, Emanuela; Sutera, Julie; Becq, Hélène; Palmieri, Ferdinando; Palmieri, Luigi; Aniksztejn, Laurent; Molinari, Florence (Frontiers in Cellular Neuroscience, 2017)
The solute carrier family SLC25 drives the import of a large diversity of metabolites into mitochondria, a key cellular structure involved in many metabolic functions. Mutations of the mitochondrial glutamate carrier SLC25A22 (also named GC1) have been identified in early epileptic encephalopathy and migrating partial seizures in infancy but the pathophysiological mechanism of GC1 deficiency is still unknown, hampered by the absence of an in vivo model. This carrier is mainly expressed in astrocytes and is the principal gate for glutamate entry into mitochondria. A sufficient supply of energy is essential for the proper function of the brain and mitochondria have a pivotal role in maintaining energy homeostasis. In this work, we wanted to study the consequences of GC1 absence in an in vitro model in order to understand if glutamate catabolism and/or mitochondrial function could be affected. First, shRNA designed to specifically silence GC1 were validated in a rat C6 glioma cells. Silencing GC1 in C6 resulted in a reduction of the GC1 mRNA combined with a decrease of the mitochondrial glutamate carrier activity. Then, primary astrocyte cultures were prepared and transfected with shRNA-GC1 or mismatch-RNA constructs using the Neon® Transfection System in order to target a high number of primary astrocytes, more than 64 %. Silencing GC1 in primary astrocytes resulted in a reduced NAD(P)H formation upon glutamate stimulation. We also observed that the mitochondrial respiratory chain was functional after glucose stimulation but not activated by glutamate, resulting in a lower level of cellular ATP in silenced astrocytes compared to control cells. Moreover, GC1 inactivation resulted in an intracellular glutamate accumulation. Our results show that mitochondrial glutamate transport via GC1 is important in sustaining glutamate homeostasis in astrocytes.